Assessing Social Capital with Respect to Urban Forms in Pakistan - et. al., Zulfiqar Ali Tariq, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we explore the social capital with respect to urban forms in Pakistan. Social capital is a concept that is recent to sociology, and both Robert Putnam and James Coleman have given attention to it over the last two decades.Putnam stresses the horizontal relationship between individuals and Coleman emphasises the vertical contribution and relationship between individuals in public organisations as the producers of social capital.As regards the notion of sustainable growth, social capital is, besides other capitals, an integral part of the services needed by a sustainable community and is considered one of the engines of development. It is important to recognise that social capital is defined by aggregation and replication. It implies the ability to aggregate it by correct use. Keeping it idle adds to its degradation and deterioration.A significant distinction between social capital and other sources of capital is seen by this fact. The key goal of this study is to examine the connection between social capital and sustainable development in Pakistan's city of Lahore. Lahore is the capital city of Pakistan and is thus regarded as one of Pakistan's least established cities opposed to more southern areas of the region. We have adopted the methodology for the chosen case studies to include deciding characteristics of urban type in Lahore. The study established crucial social sustainability characteristics that are alleged to be largely determined by neighborhood-scale facets of urban form. The research discussed several major facets of urban design; density, land usage, forms of housing, height of buildings, and accessibility. Results show a clear correlation, albeit in a particular way, between local characteristics and social development. Density and usability have proven to be key characteristics that have a major effect on social sustainability, in accordance with the outcomes of many surveys. In order to investigate the influence of other urban type characteristics, further investigations should be carried out. In order to provide a more detailed understanding of the topic, more experiments are suggested, producing more policy-oriented findings.